Embodied Mindfulness Questionnaire: Scale Development and Validation. (March 2023) - Khoury, Bassam; Vergara, Rodrigo C.; Sadowski, Isabel; Spinelli, Christina
Recently developed mindfulness scales have integrated aspects of the body in measuring mindfulness unlike other established scales. However, these scales focused solely on body awareness and did not embrace all aspects of mindfulness and the body. Specifically, they did not integrate embodiment in mindfulness. The proposed Embodied Mindfulness Questionnaire (EMQ) aims to operationalize the proposed notion of "embodied mindfulness" by grounding it into five dimensions, each representing a set of skills that can be cultivated through training and practice: (a) Detachment from Automatic Thinking, (b) Attention and Awareness of Feelings and Bodily Sensations, (c) Connection with the Body, (d) Awareness of the Mind-Body Connection, and (e) Acceptance of Feelings and Bodily Sensations. The EMQ items were developed through consultations with a panel of eight graduate students and a group of 10 experts in the field. Results from a series of three studies supported the proposed five subscales of EMQ and suggested that these subscales are independent and supported by convergent and discriminant evidence. In addition, results suggested that scores of EMQ subscales are different in terms of sensitivity to mindfulness training or meditation practice and experience. Limitations, as well as theoretical and practical implications of the EMQ subscales, are thoroughly discussed.